Study of the Closure of Sagittal Suture in Relation with Age of the Individuals tn Native of Gujarat (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Age estimation is an integral part of the biological profile employed by forensic anthropologistsin order to assist in achieving an identification of an unknown deceased individual. Its estimation is ofparamount importance and requires special attention in cases where bodies are found in decomposed,mutilated state or only fragmentary remains are discovered.Material and Method: The present study has been done on post-mortem cases referred to GMERS MedicalCollege, Himmatnagar which is referral center. Very few studies have been conducted on sagittal sutureclosure in Himmatnagar region . Total 150 post mortem cases were taken and data collected.Result: Present study reveal that Ectocranial obliteration of the various segments of the three main suturesof the skull is so inconclusive that neither does it help in estimating the age of the deceased nor does itprovide any supportive evidence in determining the age of skeletal remain. Age was determined on the basisof endocranial suture fusion.Conclusion: It was found that closure of Sagittal suture started in age of 20-29 yrs and closure completedat the age of 61 to 65 yrs.